Yacon (Smallanthus sonchifolius) beverage spontaneously fermented - Souza, Carolina Paula Gouvêa de; Pretti, Ana Claudia Frasson; Souza, Lílian Christiane da Silva; Nogueira, Luana Santos; Gomes, Ana Carolina Bianco; Scherer, Rodrigo; Lemos, Mayara Fumiere; Scolforo, Carmelita Zacchi; Bernardes, Patrícia Campos; Vasconcelos, Christiane Mileib (Semina: Ciências Agrárias, 2024)
Abstract: Yacon (Smallanthus sonchifolius) is a tuberous root with a high phenolic compounds and fibers content which has a prebiotic effect, both important for preventing and/or promoting the reduction of non-communicable chronic diseases risks. However, this root's shelf life is highly reduced and culminates the reduction of the beneficial to health compounds, which can be avoided by some strategies. In this sense, this work aimed to produce yacon beverages added with anti-browning agents (cysteine or citric acid) and evaluated the spontaneous fermentation during storage. Three yacon beverages have been produced with cysteine or citric acid (0.05% w/w) and a control beverage. Beverages were analyzed by microbiological counts, nutritional composition, physical-chemical characteristics, total phenolic compounds and phenolic acids, for 60 day storage. The data were evaluated by ANOVA and compared using the Duncan test (p≤0.05) or regression models were adjusted. Regarding microorganisms, all beverages have reached 109 CFU.ml-1 after 30 day storage. To the anti-browning agents use, the differences were occasional; however, the citric acid beverage had a desirable pH (< 4.5) for a fermented beverage, which allows inhibition of undesirable bacteria and a higher proportional initial FOS amount and less variation with 30 and 60 day storage. However, the citric acid beverage have presented smaller amount of phenolic compounds like chlorogenic and gallic acids (230.37 ± 168.63 and 40.87 ± 1.32, respectively). So, we conclued that spontaneous fermentation was a preparation technique which has added nutritional and functionals values to the yacon beverage, in special to beverage added citric acid, with a higher proportion of FOS.